2005
DOI: 10.1379/csc-58r.1
|View full text |Cite
|
Sign up to set email alerts
|

Clonogenicity of human leukemic cells protected from cell-lethal agents by heat shock protein 70

Abstract: Pretreatment of human leukemia THP-1 cells with heat shock protein Hsp70 (Hsp70) protected them from the cell-lethal effects of the topoisomerase II inhibitor, lucanthone and from ionizing radiation. Cell viability was scored in clonogenic assays of single cells grown in liquid medium containing 0.5% methyl cellulose. Colonies were observed and rapidly scored after staining with the tetrazolium salt, 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide. The frequency of abasic sites in the deoxyribonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…All these enzyme activities are stimulated by Hsp70. As expected, UDG and HAP1 activities were depressed in THP1 leukemic cells 24 h after transfection with an siRNA designed to inhibit Hsp70 (Bases 2005(Bases , 2006. Rohde et al showed that Hsp70 and its mRNA were depressed in such siRNA-transfected cells but only after a 36 h lag (Rohde et al 2006 and personal communication).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…All these enzyme activities are stimulated by Hsp70. As expected, UDG and HAP1 activities were depressed in THP1 leukemic cells 24 h after transfection with an siRNA designed to inhibit Hsp70 (Bases 2005(Bases , 2006. Rohde et al showed that Hsp70 and its mRNA were depressed in such siRNA-transfected cells but only after a 36 h lag (Rohde et al 2006 and personal communication).…”
Section: Introductionsupporting
confidence: 53%
“…Transfection A 5 nm of RNA (siRNA or scrambled RNA) was transfected in 6×10 7 cells as recommended by the manufacturer (Bases 2005(Bases , 2006.…”
Section: Deoxycytidine Deaminase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ciavarra et al (1994) reported that nuclear type I topoisomerase complexes with Hsc70 might limit heat-induced protein damage, accelerate restoration of protein function in an ATPindependent reaction, or both. Some studies showed that Hsp70 can improve base excision repair by interacting with human apurinic/apyrimidinic endonuclease and by stimulating single-strand gap-filling by DNA polymerase beta (Mendez et al 2000(Mendez et al , 2003Kenny et al 2001;Bases 2005). In a previous study, we found a significantly negative correlation between Hsp70 levels and the level of DNA damage as measured by the comet assay in workers exposed to coke oven emissions (Xiao et al 2002).…”
Section: Introductionmentioning
confidence: 70%
“…The image is formed due to the interaction of electrons when they pass through the nanoparticles. The clonogenicity of THP-1 cells has been reported, 44 and cell surface markers like CD44 expressed in THP-1 have also been studied. 45 THP-1 is one of the common cell types used for modeling cancer stem cells.…”
Section: Characterization Of Nanoparticles and Cellular Uptakementioning
confidence: 99%